2021
DOI: 10.1038/s41598-021-90880-6
|View full text |Cite
|
Sign up to set email alerts
|

Optical fibre based real-time measurements during an LDR prostate brachytherapy implant simulation: using a 3D printed anthropomorphic phantom

Abstract: An optical fibre sensor based on radioluminescence, using the scintillation material terbium doped gadolinium oxysulphide (Gd2O2S:Tb) is evaluated, using a 3D printed anthropomorphic phantom for applications in low dose-rate (LDR) prostate brachytherapy. The scintillation material is embedded in a 700 µm diameter cavity within a 1 mm plastic optical fibre that is fixed within a brachytherapy needle. The high spatial resolution dosimeter is used to measure the dose contribution from Iodine-125 (I-125) seeds. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Therefore, radiation dose could be successfully monitored by measuring the light intensity converted from the radiational energy. [ 172 , 173 ] When two methods are combined, more accurate brachytherapy can be performed. For example, an electromagnetic position sensor and radiation dose sensor with a plastic scintillation dosimeter were fused, significantly improving accuracy.…”
Section: Sensor‐integrated Robotic Surgery Toolsmentioning
confidence: 99%
“…Therefore, radiation dose could be successfully monitored by measuring the light intensity converted from the radiational energy. [ 172 , 173 ] When two methods are combined, more accurate brachytherapy can be performed. For example, an electromagnetic position sensor and radiation dose sensor with a plastic scintillation dosimeter were fused, significantly improving accuracy.…”
Section: Sensor‐integrated Robotic Surgery Toolsmentioning
confidence: 99%
“…Radiotherapy systems employing or potentially benefiting from multipoint sensing range from particle radiotherapy [1][2][3] to brachytherapy [4][5][6][7][8][9] and teletherapy [10][11][12][13]. The simultaneous, real-time monitoring of multiple points inside and outside of an irradiated volume using fibre-based sensors is currently under investigation by several groups with some success, namely in the form of the commercially available Hyperscint™ scintillator dosimeter [14]-a system that utilises a spectrometer and employs a spectral separation method to chromatically remove induced Čerenkov and fluorescence from the total signal [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Optical fiber based sensors have the small size required for insertion into BT needle applicators / catheters, allowing for potential in-vivo measurements during a procedure. Previous work by the authors have reported initial results demonstrating the potential of Gd2O2S:Tb as a scintillator for applications in LDR prostate BT [10].…”
Section: Introductionmentioning
confidence: 99%
“…This study considers the characterization of the optical fiber sensor design previously described [10], as well as additional sensor designs varying both the scintillator geometry at the tip of the sensor and the polymethyl methacrylate (PMMA) fiber core diameter. Characterization was performed using a commercial water phantom system integrated with custom 3D printed components, allowing for a more precise evaluation of sensor performance.…”
Section: Introductionmentioning
confidence: 99%